The Merkel Republic : an appraisal - Langenbacher, Eric (Berghahn Books, 2015)
"Chancellor Angela Merkel has dominated German and European politics for almost a decade. Her stellar reputation, sound political and economic management, and popularity inside of Germany resulted in one of the most decisive electoral victories for her conservative parties in postwar Germany--the country can rightfully be deemed the Merkel Republic. Bringing together German politics experts from both sides of the Atlantic, this volume addresses the campaign, results, and consequences of the 2013 Bundestag election. Chapters delve into a diverse array of themes, including immigrant-origin and women candidates, the fate of the small parties, and the prospects for the SPD, the new coalition partner, as well as more general structural trends like the Europeanization and cosmopolitanization of German politics"--Provided by publisher.